PENGARUH STRUKTUR MODAL, KEPEMILIKAN INSTITUSIONAL, DAN KINERJA KEUANGAN TERHADAP RETURN SAHAM (Kajian pada Perusahaan Properti dan Real Estate yang Tercatat di BEI Pada 2020 - 2021) - Faishal Rasyid Muzakki; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2023)
This study aims to empirically examine the effects of capital structure, institutional ownership, and financial performance on the stock return of listed property and real estate firms in the Indonesia Stock Exchange for 2020 – 2021. In this study, capital structure is proxied by the Debt-to-Equity ratio; the financial performance is proxied by the Return Equity (ROE), dan stock return is capital gain/loss in ten trading days after the financial statement release. We used multiple regression methods to analyze the data. The results show that institutional ownership and financial performance significantly affect stock returns. In contrast, the capital structure does not. Institutional ownership negatively affects stock returns, while financial performance has positive effects.